(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Helicobacter pylori (H. pylori) is a Gram-negative, microaerophilic, spiral bacterium previously known as Campylobacter pylori. It colonizes the gastrointestinal mucosa of its host in spite of a strong, persistent humoral and cellular immune response to H. pylori at the local and systemic level; the organism persists for the lifetime of its host. This study was aimed at evaluating cellular immune response (CD4 and CD8) to H. pylori infection. The results recorded a significant increase in local and systemic CD4 of patients compared with control; moreover, local CD4 increased more than systemic, while CD8 did not show any significant differences either locally nor systemically. No significant differences were found between males and females and also between age groups for all parameters, while CD4 was significantly increased in all age groups and gender groups compared with the control. Local concentration of CD4 reached a maximum level in duodenal ulcer while minimum concentration was shown in chronic gastritis. Both CD4 and CD8 concentration were homogenized in patients with different infection types.